Competing risks models - Gerard J. van den Berg (Institute for Labour Market Policy Evaluation (IFAU), 2005)
A competing risks model is a model for multiple durations that start at the same point of time for a given subject, where the subject is observed until the first duration is completed and one also observes which of the durations is completed first. This article gives an overview of the main issues in the empirical econometric analysis of competing risks models. The central problem is the non-identification of dependent competing risks models. Models with regressors can overcome this problem, but it is advisable to include additional data. Alternatively, effects of interest can be bounded.
Keywords: C41; C51; J64; 330; competing risks; duration model; duration variable; censoring; mixed proportional hazard model; latent durations; hazard rate; unemployment duration; identification; multiple spells; bounds; regressors; unobserved heterogeneity; selection; Arbeitslosigkeit; Theorie; Statistische Bestandsanalyse